Inhibition of Alcoholic Fermentation of Grape Must by Fatty Acids Produced by Yeasts and Their Elimination by Yeast Ghosts - Lafon-Lafourcade, S. (1984)
In a complete nutritive medium rich in sugar, such as grape must, the inhibition of alcoholic fermentation is caused by substances produced by the yeast which, acting synergistically with ethanol, are toxic to the yeasts themselves. Among these are decanoic and octanoic acids and their corresponding ethyl esters. Their adsorption by yeast ghosts permits the prevention and treatment of fermentation stoppages.